From Symbolic to Substantive: The Role of Women Legislators in Local MSME Policy (Jurnal Bina Praja, 2025)
This study analyzes the role of Women legislators of Commission II local legislative in Pasuruan city in promoting the empowerment of micro, small, and medium enterprises (MSME). Using a qualitative case study approach and guided by the Actor Network Theory (ANT), this research highlights structural constraints and weak interconnections among policy actors. Data was collected through interviews, observations, and documentation. Findings show that women legislators often play symbolic roles due to male-dominated power structures, limited institutional support from political parties, and minimal access to strategic forums involving local technical agencies (OPD) and MSME communities. While their advocacy style tends to be empathetic and community-based, it remains disconnected from formal decision-making processes. ANT analysis demonstrates that women legislators have not yet become strategic nodes within the policy network. To shift from symbolic to substantive representation, it is essential to enhance their political capacity, improve institutional support, and strengthen inter-actor collaboration. These efforts will contribute to more inclusive and gender-responsive MSME policies.
Keywords: Women Legislators; Actor Network Theory; Political Representation; MSME Policy